Development of a Digital Radiation Card Model Using an Android-Based Smartphone for Patients Undergoing External Radiation Therapy - Rukmayani Sipahutar; Kusworo Adi; Agung Nugroho Setiawan; Gatot Murti Wibowo; Nanang Sulaksono (International Journal of Health and Medicine, 2026)
The clinical role of radiotherapy in oncology, where ionising radiation is applied to damage the deoxyribonucleic acid (DNA) structure of tumour target cells in order to halt uncontrolled cell proliferation. The success of radiotherapy is influenced by patient compliance in completing the entire course of treatment according to the prescribed schedule. Consequently, the aim of this study was to develop a digital radiation card model using an Android-based smartphone for patients undergoing external radiation therapy at Murni Teguh General Hospital in Medan, with a view to improving patient compliance and satisfaction. This study employed a Research and Development (R&D) approach to develop an Android-based digital radiation card and assess its feasibility. The R&D method was chosen as it is suitable for research that produces a product whilst simultaneously conducting testing and refinement prior to wider implementation. The ADDIE development model was utilised, comprising five stages: Analysis, Design, Development, Implementation, and Evaluation. Based on the expert validation test, the digital radiotherapy card has been found to be effective in improving patient compliance and satisfaction in the radiotherapy department. The effectiveness of using Android-based digital radiation cards for patients undergoing external radiation therapy in improving patient satisfaction is demonstrated by the results of the Wilcoxon test, which show that all items relating to satisfaction have a p-value < 0.05; this indicates a significant difference between pre-test and post-test scores for satisfaction following the implementation of the Android-based digital radiation cards. The effectiveness of using Android-based digital radiation cards for patients undergoing external radiation therapy in improving patient compliance was demonstrated by the results of the Wilcoxon test, which showed that all items relating to compliance had a p-value < 0.05. Consequently, the use of digital radiation cards can be deemed effective in improving respondents’ compliance.